Hasil Tanaman Tomat Melalui Interval Pemberian Air serta BioVAM pada Ketersediaan Air Sebagai Faktor Pembatas - Abdullah Sarijan; Adrianus Adrianus (Musamus Journal of Agrotechnology Research, 2019)
The aim of this research is to modify the environment that lacks water, especially during the dry season. The study was conducted by taking into account the conditions in Merauke-Papua where during the dry season water becomes a limiting factor in crop cultivation activities. The study was conducted at the Screen House of the Faculty of Agriculture, Musamus University, Merauke in September to December 2013, designed in a Randomized Block Design consisting of 4 treatments for Water Provision Intervals and BioVAM with 3 replications so that there were 12 experimental units. Each experimental unit contained 12 plants and used 50% of them as sample plants. The results showed that the Water Delivery Interval affected the growth and production of tomato plants. The treatment of water every day produces the best growth and production compared to other treatments, but because the study is directed to address water as a limiting factor in the dry season, for the cultivation of tomato plants, water supply is recommended to be carried out at intervals of no more than 3 days. Production of tomatoes produced from the treatment of water every day is 6221.43 g per plot (10.369 tons per hectare), the treatment of giving water every third day is 3205.47 g per plot (5.342 tons per hectare), from the treatment of giving water every the fifth day was 1205.85 g per plot (2,009 tons per hectare), and the production resulting from the treatment of water every seventh day was 590.50 g per plot (0.984 tons per hectare). The results of this study do not yet reflect the actual situation in the field, so it is necessary to conduct a similar study in the field with a tighter treatment interval and a more appropriate volume of water. Keywords: fungal hyphae, drought stress, mycorrhoea